1987
DOI: 10.1128/mcb.7.7.2329
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination between single-stranded DNA and chromosomal genes in Saccharomyces cerevisiae.

Abstract: Transformation of Saccharomyces cerevisiae strains was examined by using the URA3 and TRPI genes cloned into M13 vectors in the absence of sequences capable of promoting autonomous replication. These constructs transform S. cerevisiae ceUls to prototrophy by homologous recombination with the resident mutant gene. Single-stranded DNA was found to transform S. cerevisiae cells at efficiencies greater than that of doublestranded DNA. No conversion of single-stranded transforming DNA into duplex forms could be det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 25 publications
3
25
0
1
Order By: Relevance
“…These results strongly suggest that inactivation of unlinked duplicated met2 genes through crosses also is due to cytosine methylation and results from the same process as that operating on tandemly duplicated met2 sequences. (20). Using M13 constructs in opposite orientations, we have found that the two DNA strands behave equally in transformation.…”
Section: Resultsmentioning
confidence: 95%
“…These results strongly suggest that inactivation of unlinked duplicated met2 genes through crosses also is due to cytosine methylation and results from the same process as that operating on tandemly duplicated met2 sequences. (20). Using M13 constructs in opposite orientations, we have found that the two DNA strands behave equally in transformation.…”
Section: Resultsmentioning
confidence: 95%
“…Gene targeting using single-stranded DNA (ssDNA) has successfully been carried out on Saccharomyces cerevisiae (33). The authors have not only shown that gene targeting with ssDNA is possible, they also provided some evidence that ssDNA is more efficient than targeting with double-stranded DNA (dsDNA).…”
Section: ϫ6mentioning
confidence: 90%
“…White and J. E. Haber, personal communication). (iii) Single-stranded DNA is recombinogenic in yeast following transformation (28). (iv) Mismatch correction is involved in mitotic and meiotic gene conversion in yeast (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%